Associations between Johne’s Disease and fertility in UK dairy herds - Reynolds, Jessica (2024)
The objective of this observational study was to quantify the association between Mycobacterium avium subspecies paratuberculosis (MAP) antibody status and risk of insemination and subsequent conception, in UK dairy cattle. Longitudinal milk recording, fertility and MAP antibody enzyme-linked immunosorbent assay (ELISA) milk test data were collated retrospectively from 121,762 lactations in 78 herds. Datasets were structured into appropriate units to suit outcomes and enable temporal association between current and future MAP status, and fertility measures. Current MAP status was categorised according to most recent status within 180 days, with time-related future MAP status assigned based on MAP antibody ELISA milk test data for each cow. Multilevel multivariable logistic regression models were used to evaluate associations between MAP status and 21-day pregnancy and submission rate and conception risk. Posterior predictions and cross-validation techniques were used to assess model fit and check model building assumptions.